2013
DOI: 10.4317/medoral.18465
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pregnancy on orthodontic tooth movement in rats

Abstract: Introduction: The purpose of this study was to investigate the effect of pregnancy on orthodontic tooth movement in Wistar rats. Material and Methods: Forty eight female three-month old Wistar rats with an average weight of 250±25 gr were selected and randomly divided into two experimental (pregnant) and control groups (non-pregnant). Maxillary central incisors were tipped distally by insertion of springs exerting 30g force. Two, seven and fourteen days after spring insertion animals were sacrificed. Then the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
1
11
0
3
Order By: Relevance
“…This opinion is in accordance with Sirisoontorn et al 3 research which revealed that lack of estrogen may increase the orthodontic tooth movement. That results is same as some previous studies such as Haruyama et al, 9 Ghajar et al, 10 and Olyaee et al, 11 which said that estrogen level inversely related to orthodontic tooth movement.…”
Section: Methodssupporting
confidence: 92%
“…This opinion is in accordance with Sirisoontorn et al 3 research which revealed that lack of estrogen may increase the orthodontic tooth movement. That results is same as some previous studies such as Haruyama et al, 9 Ghajar et al, 10 and Olyaee et al, 11 which said that estrogen level inversely related to orthodontic tooth movement.…”
Section: Methodssupporting
confidence: 92%
“…Two studies showed more movement in the pregnant animals [44,45] while no difference was observed in the third [43] (Fig. 2).…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 89%
“…After the exclusion of one more paper because it involved animals with dietary calcium deficiency [42], four papers were considered eligible ( Fig. 1) [43][44][45][46].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modifications in periodontal tissues result in bone remodeling, which is crucial for orthodontic tooth movement. [2][3][4] By now, many studies have investigated various ways of accelerating tooth movement, including injections of the drug, electric stimulation, corticotomy, pulsed electromagnetic fields, and mechanical and physical methods. 5,6 In clinical practice, low-level laser therapy (LLLT) is widely used.…”
Section: Introductionmentioning
confidence: 99%